Performance Evaluation of Locally-Produced Waste Cooking Oil Biodiesel with Conventional Diesel Fuel - Khaskheli, A. A.; Walasai, G. D.; Jamali, A. S.; Jamali, Q. B.; Siyal, Z. A.; Mengal, A. (Engineering, Technology & Applied Science Research, 2018)
Increasing environmental concerns forced us to look for cheaper, reliable and secure sources of energy. Fossil fuels like oil, coal, and natural gas are having limited supplies and are depleting fast. Both energy security and environmental concerns have resulted in inclination towards renewable energy sources. Biodiesel does not contain petroleum, but it can be blended with petro-diesel in various mix levels. This research investigated biodiesel produced by the use of cheap waste cooking oil, collected from the local market of Nawabshah, Pakistan. The collected waste oil was converted into biodiesel by trans-esterification process at PCSIR Laboratory, Karachi. The fuel samples were tested in a diesel engine test bed unit at the Thermodynamics Laboratory of Quaid-e-Awam University. Biodiesel blends were compared with the conventional diesel fuel. The comparative analysis of the performance parameters concluded that brake specific fuel consumption of B30 (biodiesel 30%+diesel 70%) mix was 6.9% higher than that of 100% diesel. The brake thermal efficiency of B30 decreased about 4.75% in comparison with conventional diesel.